Comparison of biofilm ecology supporting growth of individual Naegleria species in a drinking water distribution system. Issue 4 (21st February 2017) - Puzon, Geoffrey J.; Wylie, Jason T.; Walsh, Tom; Braun, Kalan; Morgan, Matthew J.
Abstract: Free-living amoebae (FLA) are common components of microbial communities in drinking water distribution systems (DWDS). FLA are of clinical importance both as pathogens and as reservoirs for bacterial pathogens, so identifying the conditions promoting amoebae colonisation of DWDSs is an important public health concern for water utilities. We used high-throughput amplicon sequencing to compare eukaryotic and bacterial communities associated with DWDS biofilms supporting distinct FLA species ( Naegleria fowleri, N. lovaniensis or Vermamoeba sp. ) at sites with similar physical/chemical conditions. Eukaryote and bacterial communities were characteristics of different FLA species presence, and biofilms supporting Naegleria growth had higher bacterial richness and higher abundance of Proteobacteria, Bacteroidetes (bacteria), Nematoda and Rotifera (eukaryota). The eukaryotic community in the biofilms had the greatest difference in relation to the presence of N. fowleri, while the bacterial community identified individual bacterial families associated with the presence of different Naegleria species. Our results demonstrate that ecogenomics data provide a powerful tool for studying the microbial and meiobiotal content of biofilms, and, in these samples can effectively discriminate biofilm communities supporting pathogenic N. fowleri. The identification of microbial species associated with N. fowleri could further be used in the management and control of N. fowleri in DWDS. Abstract : This study reports on pipe wall biofilm ecology supporting the presence of pathogenic and non-pathogenic Naegleria spp. in an operational drinking water distribution system.